Simultaneous Determination of Eight Active Compounds in Baitouweng Decotion and its Single Herbs. (31st March 2019) - Wang, Yubo; Xu, Qianqian; Shen, Zhiqiang; Wang, Yanping; Dong, Lin; Fu, Shijun; Yang, Limei; Qin, Mimi; Zhang, Ying; Guo, Shijin
Abstract: Baitouweng Decotion (BD) is a famous traditional Chinese medicinal prescription, which is composed of Pulsatilla chinensis (bunge) regel, Coptis chinensis franch ., Phellodendron chinense and Cortex Fraxini . In this study, a simple and sensitive high performance liquid chromatography coupled with ultraviolet detection method was established for the simultaneous determination of eight marker compounds including Esculin, Fraxin, Esculetin, Fraxetin, Columbamine, Coptisine, Palmatine Chloride and Berberine hydrochloride in BD, the single herbs and their negative controls. The chromatographic separation was performed using an Agilent Eclipse XDB-C18 column with a gradient elution system of acetonitrile and 0.1% phosphoric acid (contained 0.2% triethylamine) solution at a flow rate of 0.8 mL/min. The results demonstrated that the validated method was simple, reliable and successfully applied to evaluate the selected compounds in water extraction (BDW) and ethanol extraction (BDE) of BD, the single herbs and their negative control for quality control. Moreover, the experimental data showed that the contents of the major active components detected in BDE were significantly higher than those in the BDW, while the BDW had several peaks BDE without. The paper also suggested a method to extract Fraxin, Esculin, Fraxetin, Esculetin and Berberine from Baitouweng Decotion more effectively.